Hubungan Repetitive Motion dan Masa Kerjadengan Kejadian Carpal Tunnel Syndrome pada Penjahit di Kelurahan Belian Kota Batam - Mariaman Tjendra; Indria Sari; Heni Febryanti (Universitas Batam, 2022)
Background :Carpal tunnel syndrome is a collection of symptoms due to compression of the median nerve in the carpal tunnel at the wrist, one of the risk factors for the occurrence of carpal tunnel syndrome, namely repetitive motion and working period. The purpose of this study was to determine the relationship between repetitive motion and tenure with the incidence of carpal tunnel syndrome in tailors. Method :This type of research is an analytic study with a cross sectional approach conducted on tailors in Belian Village, Batam City. The sampling technique was simple random sampling with a total sample of 44 respondents. The results of the study were analyzed by chi-square. Result :From the results of the calculation of the chi square test, the results obtained with a value of p = 0.001 (p 0.05), namely there is a relationship between years of service and the incidence of carpal tunnel syndrome in tailors and the results are obtained with a value of p = 0.002 (p 0.05), namely there is The relationship between repetitive motion and the incidence of carpal tunnel syndrome in tailors in Belian Village, Batam City Conclusion :Based on this research, there is a relationship between repetitive motion and length of service with the incidence of carpal tunnel syndrome in tailors in Belian Village, Batam City in 2021.